Exploring microbial diversity responses in agricultural fields: a comparative analysis under pesticide stress and non-stress conditions - Gangola, Saurabh; Joshi, Samiksha; Bhandari, Geeta; Pant, Garima; Sharma, Anita; Perveen, Kahkashan; Bukhari, Najat A.; Rani, Ranjana (Frontiers in Microbiology, 2023)
Exposure of pesticides changes the microbial community structure in contaminated agricultural fields.To analyze the changes in the native microbial composition qRT-PCR and the metagenomic study was conducted. qRT-PCR results observation exhibited that the uncontaminated soil having higher copy number of 16S rDNA in relative to the soil contaminated with pesticide. Metagenome analysis interprets that uncontaminated soil is enriched with proteobacteria in comparison to pesticide-contaminated soil.However, the presence of actinobacteria, firmicutes, and Bacteroides was found to be dominant in the pesticide-spiked soil. Additionally, the presence of new phyla such as chloroflexi, planctomycetes, and verrucomicrobia was noted in the pesticide-spiked soil, while acidobacteria and crenarchaeota were observed to be extinct. These findings highlight that exposure of pesticides on soil significantly impacts on the biological composition of the soil. The abundance of microbial composition under pesticide stress could be of better use for the treatment of biodegradation and bioremediation of pesticides in contaminated environments.